A new technique for the reconfiguration of radial distribution network for loss minimization - Shamsudin, Nur Hazahsha; abidullah, Noor Athira; Abdullah, Abdul Rahim; Sulaima, Mohamad Fani; Jaafar, Hazriq Izzuan (Engg Journals Publications, 2014)
Over 50 years Malaysia is using the same power transmission channel from the colonial of the British. It is very old and needs some improvement especially in distribution network system. An increment of load demand and losses occurrences in distribution network system have worsen the existing condition. Pertaining to that, a reconfiguration of the distribution network is introduced to resolve the problem. In this paper, a new technique called as Improved Genetic Algorithm (IGA) for reconfiguring distribution network simultaneously implemented with the placement of small scale power generation or Distributed Generation (DG) is presented. Both conventional and improved genetic algorithms are employed within parameter constraint to be significantly compared in response to power losses and voltage profile performances. The algorithm process is initially started with the search solution for the best switching combinations throughout 33 IEEE distribution bus systems. The results convey a better improvement in performance of the improved method compared with the genetic algorithm (GA).